Antigenic epitope targets of rhesus macaques self-curing from Schistosoma mansoni infection - Vance, Gillian M.; Khouri, Mariana I.; Neto, Almiro Pires da Silva; James, Sally; Leite, Luciana C. C.; Farias, Leonardo Paiva; Wilson, R. Alan (Frontiers in Immunology, 2024)
The self-cure of rhesus macaques from a schistosome infection and their subsequent strong immunity to a cercarial challenge should provide novel insights into the way these parasites can be eliminated by immunological attack. High density arrays comprising overlapping 15mer peptides from target proteins printed on glass slides can be used to screen sera from host species to determine antibody reactivity at the single epitope level. Careful selection of proteins, based on compositional studies, is crucial to encompass only those exposed on or secreted from the intra-mammalian stages, and is intended to focus the analysis solely on targets mediating protection. We report the results of this approach using two pools of sera from hi and lo-responder macaques undergoing self-cure, to screen arrays comprising tegument, esophageal gland and gastrodermis proteins. We show that overall, the target epitopes are the same in both groups but the intensity of response is twice as strong in the high responders. In addition, apart from Sm25, tegument proteins elicit much weaker responses than those originating in the alimentary tract, as was apparent in IFNγR KO mice. We also highlight the most reactive epitopes in key proteins. Armed with this knowledge, we intend to use multi-epitope constructs in vaccination experiments which seek to emulate the self-cure process in experimental animals, and potentially in humans.